Mitochondrial genotype modulates mtDNA copy number and organismal phenotype in Drosophila - Salminen, Tiina S. (2017)
We evaluated the role of natural mitochondrial DNA (mtDNA) variation on mtDNA copy number, biochemical features and life history traits in Drosophila cybrid strains. We demonstrate the effects of both coding region and non-coding A +T region variation on mtDNA copy number, and demonstrate that copy number correlates with mitochondrial biochemistry and metabolically important traits such as development time. For example, high mtDNA copy number correlates with longer development times. Our findings support the hypothesis that mtDNA copy number is modulated by mtDNA genome variation and suggest that it affects OXPHOS efficiency through changes in the organization of the respiratory membrane complexes to influence organismal phenotype. (C) 2017 Elsevier B.V. and Mitochondria Research Society. All rights reserved.